WORKING WITH ARRAYS AND LISTS IN PYTHON AND C++ PROGRAMMING LANGUAGES - Shamsiddinova Maftunabonu Ulug’bek qizi (Journals Park Publishing, 2024)
This article examines the strengths and weaknesses of the C++ and Python programming languages, their efficiency and usability for working with lists and arrays. Principles for implementing convenient methods for working with lists are presented.
Keywords: C , Python programming language, list, working with lists, string, efficient integration, GUI, C programming language.